Determination of Elemental Variations in Tea Leaves (Camellia sinensis L) in Different Harvest Time by WDXRF Spectrometry - Ercisli, S.; Demir, F.; Budak, G.; Karabulut, A. (Asian Journal of Chemistry, 2010)
The percentage of elements in different harvest time in fresh green tea leaves (Camellia sinensis) clone Derepazari-7 grown in Rize region of Turkey were determined semi quantitatively by using wave-dispersive X-ray fluorescence spectrometry (WDXRF). A qualitative analysis of spectral peaks showed that 15 mineral and trace elements (P, K, Ca, Mg, S, Cl, Mn, Zn, Al, Fe, Si, Rb, Cu, Ni and Sr) were presented in the fresh green leaves of tea (Camellia sinensis) clone Derepazari-7. The amounts of P, K, Cl and Ni in fresh green leaves were the highest at 1st harvest time and decreased continuously to 3rd harvest time. In contrast, the amount of Ca, Mg, S, Al, Fe and Sr were the lowest at 1st harvest time and continuously increased from 1st harvest to 3rd harvest time.